Conservation ecology of the Cape clawless otter, Aonyx capensis, in an urban environment - Okes, Nicola Catherine (Department of Biological Sciences, 2018)
Coastal cities have impacted negatively on freshwater and marine ecosystems - primarily through habitat loss, fragmentation and pollution. Globally, it has been found that otter's dependence on these ecosystems exposes them to a myriad of threats, including loss of habitat, human-wildlife conflict and the bioaccumulation of toxic pollutants. The Cape clawless otter, Aonyx capensis, is the most widely distributed otter species in southern Africa and persists in human-modified habitats, including large cities. The Cape Peninsula provides a unique opportunity to study the impacts of urbanisation on otters as it presents a gradient from densely populated urban areas in the north (City of Cape Town) to sparsely populated areas interspersed with large expanses of natural habitat (Table Mountain National Park) in the south. In this thesis, I investigate the distribution, diet and threats to otters living on the Cape Peninsula. I use sign-based occupancy surveys to determine both broad and fine scale drivers of otter presence within the Peninsula's river systems and predicted that otters would avoid densely populated urban areas and rivers or sections thereof that are heavily transformed and polluted. I collected spraint from living otters and vibrissae from dead otters to investigate their diet. I predicted that otters would show an increased reliance on marine foods in areas where freshwater habitats were degraded in addition to seasonal variation in diet associated with the marked seasonal variation in rainfall and primary productivity typical of temperate Mediterranean ecosystems. I explored both immediate and long-term threats to otters by collating all records of conflict, injury and mortality reported over 5 years in addition to determining PCB levels from road-killed otters. Contrary to my predictions, otters did not avoid urban areas, and were more frequently detected in transformed lowland freshwater river systems close to Marine Protected Areas (MPA). Within rivers otters avoided the relatively pristine, yet unproductive, upper reaches of rivers as well as canalised sections and those with consistently high E.coli counts. I found that otters were feeding on both marine and freshwater prey in both polluted and nonpolluted systems. Where large, transformed lowland wetlands were in close proximity to MPAs, otter diet consisted largely of a combination of freshwater crabs and exotic fish from the polluted systems as well as marine fish and rock lobster from the relatively unpolluted MPA. Isotope results complemented the faecal analyses and confirmed that otters show significant variation in diet between seasons, sites and individuals, suggesting an opportunistic and generalist foraging strategy. Importantly, the dietary results reinforce the distribution model that otters rely heavily on the interface between coastal and lowland wetland and river ecosystems close to the MPA, for both foraging and breeding habitat. However, these are the areas that are transformed and heavily impacted by urban development, and therefore the area where otters would most likely be at risk. I developed a hotspot map of otter conflict across the Peninsula and found that the Peninsula otter population experiences low to moderate levels of conflict throughout most of their current range. High conflict areas are associated with optimal habitat that has been fragmented by canalisation and urban development. Road-killed otters showed signs of accumulation of PCBs in liver tissue suggesting that despite otters being adaptable generalists, their dependence on polluted freshwater systems may have long-term health impacts. Mitigating these threats is possible with improved urban planning, waste water treatment and education of the public. However the success of these approaches requires long-term monitoring which is unlikely to be prioritised by resource constrained conservation authorities. I thus explored whether the large citizen science community in Cape Town can be used to monitor the population. I used Maxent to model otter distribution using citizen reported sightings over 5 years and compared the results with the occupancy model outputs. The predicted Maxent distribution mirrored that provided by occupancy models, and highlighted further areas of suitable otter habitat and routes for dispersal. Together my findings suggest that Cape clawless otters, like many other meso-carnivores in South Africa and globally, display a remarkable ability to adapt to human-modified environments using the interface between degraded freshwater systems and the inshore region to feed on a diverse range of prey. Of concern are the moderate to high levels of conflict with people and dogs, vehicle accidents and the accumulation of toxins. Long-term monitoring of the population and the effect of proposed interventions can be achieved by creating a platform for citizen sightings to be recorded in perpetuity at low cost. This platform can also serve as tool for educating the public on the global challenges of conserving biodiversity within and adjacent to large cities.